I want it all and I want it now: Irrational beliefs and dark tetrad traits in men - Volarov Marija; Velimirović Mina; Kovač Jovana; Baić Valentina; Tovilović Snežana (University Educons, Faculty of Sports and Tourism, Novi Sad, 2022)
The Dark Tetrad (DT) - an umbrella term for four socially aversive traits (Machiavellianism, narcissism, psychopathy, and sadism) gained a lot of research interest. However, little is known about how these traits are related to cognitive constructs such as hostile interpretation bias (HIB) and low frustration tolerance (LFT). In an attempt to explain what could contribute to understanding the development of DT, the present study aimed to combine two different theoretical perspectives: a theory underlying CBT and a trait-based model of personality. The study used a community sample of men (N = 612) to test whether LFT (a) predicts HIB and the expression of DT traits and (b) has an indirect, mediated by HIB, effect on DT traits. Results showed a significant direct effect of LFT on all four DT traits. Also, the indirect effect was significant in all four tested models. It might be that, by seeking schema confirmation, individuals gradually develop a stable pattern of behavioral, emotional, motivational reactions, labeled as (DT) traits. HIB seems to be an integral part of the assimilation process, by mediating the relationship between LFT and all four DT traits.